Cooperatives as Sustainability Intermediaries: Rebuilding Smallholder Palm Oil Governance, Welfare, and Inclusive Certification in Indonesia - Loso Judijanto (PT. Anagata Sembagi Education, 2026)
Indonesia’s palm oil sector is central to rural livelihoods, export earnings, and agrarian transformation, yet it remains deeply contested because of concerns over deforestation, land conflict, social inequality, certification gaps, and smallholder exclusion from sustainable value chains. Smallholders are indispensable to any credible palm oil sustainability agenda because they manage a substantial share of oil palm landscapes and supply a significant proportion of fresh fruit bunches, but many remain constrained by insecure land legality, low productivity, aging palms, weak access to finance, fragmented marketing, limited technical assistance, and costly certification requirements. This article uses a qualitative literature review, rather than a systematic literature review, to synthesize recent scholarship on the role that cooperatives should play in supporting sustainable smallholder palm oil in Indonesia. The article argues that cooperatives should be repositioned from conventional marketing or administrative bodies into “sustainability intermediaries” capable of linking farmer welfare, legality, certification, traceability, agronomic upgrading, environmental stewardship, and democratic village-level governance. The review identifies six expected roles of cooperatives: democratic and professional farmer-owned institutions; legality and certification hubs; productivity and replanting platforms; fair and traceable market intermediaries; village-level sustainability platforms; and welfare-oriented rural enterprises. The article concludes that sustainable smallholder palm oil cannot be achieved through certification pressure alone; it requires cooperative-centered institutional reform that makes sustainability materially beneficial for smallholders and socially embedded in palm oil-producing villages